Halogen Bonding Increases the Potency and Isozyme Selectivity of Protein Arginine Deiminase 1 Inhibitors. (1st August 2019) - Mondal, Santanu; Gong, Xuefeng; Zhang, Xiaoqian; Salinger, Ari J.; Zheng, Li; Sen, Sudeshna; Weerapana, Eranthie; Zhang, Xuesen; Thompson, Paul R.
Abstract: Protein arginine deiminases (PADs) hydrolyze the side chain of arginine to form citrulline. Aberrant PAD activity is associated with rheumatoid arthritis, multiple sclerosis, lupus, and certain cancers. These pathologies established the PADs as therapeutic targets and multiple PAD inhibitors are known. Herein, we describe the first highly potent PAD1‐selective inhibitors (1 and 19 ). Detailed structure–activity relationships indicate that their potency and selectivity is due to the formation of a halogen bond with PAD1. Importantly, these inhibitors inhibit histone H3 citrullination in HEK293TPAD1 cells and mouse zygotes with excellent potency. Based on this scaffold, we also developed a PAD1‐selective activity‐based probe that shows remarkable cellular efficacy and proteome selectivity. Based on their potency and selectivity we expect that 1 and 19 will be widely used chemical tools to understand PAD1 biology. Abstract : Der iodabhängige Anstieg der Wirksamkeit und Isozymselektivität von Protein‐Arginin‐Deiminase‐1(PAD1)‐Inhibitoren wurde erforscht. Iodatome bilden eine Halogenbindung mit PAD1. Aufgrund der hohen Lipophilie von Iod zeigen diese Inhibitoren eine ausgezeichnete zelluläre Aktivität. Mit diesem Grundgerüst wurde eine PAD1‐selektive chemische Sonde mit überlegener zellulärer Wirksamkeit entwickelt.